Profitability determinants of Islamic banking schemes and conventional banking schemes in Malaysia - Isa, Mohamad Yazid (Universiti Utara Malaysia, 2006)
This study examines the profitability determinants of Islamic banking schemes and interest banking schemes in Malaysia.In order to examine the determinants of bank profitability, this study focuses on the Return on Asset (ROA) and Return on Deposit (ROD) which assumed to be a function of bank characteristics as internal factors and macroeconomic variables as the external factors.This study found that overhead cost, equity capital and loan loss provision play important roles in determining bank profitability.Meanwhile economic variables such as Gross Domestic Product (GDP) and interest rate have no significant impact on profitability of both schemes.